Behavior Analysis on PLN Mobile Users Using UTAUT Method - Paramita S., Amanda; Pratama, Arista; Wulansari, Anita (Kresnamedia Publisher, 2022)
The advancement of information technology is currently accelerating in all aspects of life. The presence of information technology, which is constantly evolving, makes it easier for users to use information systems. Technological advancements show that information technology is not currently required for businesses or organizations. PT. PLN (Persero) is a State-Owned Enterprise (BUMN) in the electricity sector that controls, supplies, and serves the community's electricity needs. PT. PLN (Persero) is committed to improving electricity services for all customers. PT. PLN (Persero) provides innovation through the PLN Mobile Application to improve electrical services. The PLN Mobile Application provides users with up-to-date information on electricity services, allows them to register independently based on their needs, and calculates costs. This research aimed to identify the behavioral factors influencing users' acceptance of the PLN Mobile Application. The UTAUT model was used for the research, and it was modified with seven variables: performance expectation, effort expectation, social influence, facilitating conditions, trust, information quality, and behavioral Intention. Sampling using the Probability Sampling Technique, with Random Sampling as the sampling type. The sample size was 400 Surabaya City respondents who used the PLN Mobile Application. SEM-PLS and SmartPls 3 software were used to analyze research data. According to the research finding, the factors influencing Behavioral Intention or user behavior on the PLN Mobile Application were Performance Expectancy, Effort Expectancy, Facilitating Conditions, and Social Influence (p-value 0, 05). In contrast, Trust and Information Quality had no positive and insignificant effect on Behavioral Intention.